A cadaveric study of variations in the origin of medial circumflex femoral artery (International Journal of Biomedical and Advance Research, 2015)
The medial circumflex femoral artery is the chief source of blood supply to head and neck of femur. So, the precise knowledge of the anatomy of the artery is essential during reconstructive surgeries of the hip joint and if it is damaged, may cause avascular necrosis of the head of femur.